ALIH KODE DALAM BAHASA INGGRIS PADA PROGRAM TV INDONESIA NEZ ACADEMY - SUALANG, ENJELIN HANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This skripsi is the title of ?Alih Kode dalam Bahasa Inggris pada Program TV Indonesia Nez Academy?. Is analyzed from the sociolinguistics view. The aims of this research are to identify, classify, and describe the code switching used by its host, Boy William, and its judge leader, Agnes Monica in the program Nez Academy (Talent show program on NET. TV channel). The research uses descriptive method, by using the theory of Romaine (1995:122) and Hoffman (1992). The data were collected from utterances containing code switching in English by Agnes Monica and Boy William, in 16 episodes. The total number of code switching found are 239 by Agnes Monica and Boy William in Indonesia TV program Nez Academy. The results of this research show that there are three types of code swiching they are: Inter-sentensial switching, Intra-sentensial switching and Tag switching. The results of this research also show that there are seven reasons which influence the use of code switching in Indonesia TV program Nez Academy, namely talking about a particular topic with, showing empathy about something, interjection (inserting sentence fillers or sentence connector), repetition used for clarification, repetition used for clarification and Expressing group identity. However, quoting somebody else was not found in the data. Keywords: Code switching, Indonesian TV program NEZ Academy, Sociolinguistics.